Expressive Speech Acts of Sadness in The Diary of a CEO Podcast: Integrating Speech Act Theory and Cognitive Appraisal - Dwi Zahara Nuraisyah; Dadan Rusmana; Andang Saehu (English Language in Focus (ELIF), 2026)
Expressive speech acts are commonly used to communicate speakers' emotions in everyday interaction, including podcast conversations that encourage personal storytelling. However, little attention has been paid to how sadness is expressed through speech acts and how these expressions relate to speakers' cognitive appraisal of loss. This study examines expressive speech acts of sadness in selected episodes of The Diary of a CEO Podcast. Specifically, it identifies expressions of sadness, classifies the underlying forms of harm and loss based on Lazarus and Folkman's (1984) Cognitive Appraisal Theory, and analyses how sadness is realized through direct and indirect speech acts. This study employed a qualitative content analysis design. The data consisted of 38 utterances expressing sadness produced by three podcast guests: Simon Cowell, Mo Gawdat, and Liam Payne. The utterances were analysed using Searle's Speech Act Theory and Lazarus and Folkman's Cognitive Appraisal Theory. The findings identified six appraisal categories of sadness: Loss of a Loved One, Loss of Identity, Loss of Self-esteem or Social Esteem, Loss of Something Personally Valued, Loss of a Meaningful Relationship, and Loss of a Valuable Goal or Commitment. Loss of a Loved One was the most frequent category, indicating that bereavement was the primary source of sadness in the selected podcast episodes. In terms of speech act realization, 35 utterances (92.1%) were expressed through direct speech acts, whereas only 3 utterances (7.9%) were expressed indirectly. These findings contribute to pragmatic research by showing that expressive speech acts of sadness are shaped by both speakers' cognitive appraisal of harm and loss and their linguistic choices. By integrating Speech Act Theory with Cognitive Appraisal Theory, this study provides a broader understanding of emotional communication in naturally occurring podcast discourse.